Intelligent robotic devices using knowledge from the cloud - Gonçalves, P.J.S. (2020)
In this paper are presented several low-cost solutions to deploy Robots in selected environments and perform complex tasks, by using the Cloud. The Cloud can be used as a database or a powerful processor to extend the robots capabilities in the field. Intelligent Robots can take advantage of a distributed, web-based information system deployed in the cloud to perform high level tasks. This paper proposes a robotic control framework suited to be used by low-cost robots, performing teleoperated and/or autonomous tasks. The first part is dedicated to the development of an Android based robot control framework. This framework connects to specific low- level controllers that were developed for QuadCopters, wheeled and tracked mobile robots. The second part is dedicated to ”place” the Android based robot in the cloud. There, the robot can perform Cloud based highly automated intelligent tasks in order to optimize their use and take best advantage of previous knowledge mod- els, e.g., objects databases or 3D world models. Also, the robot can be controlled remotely using a classical teleoperation mode, using wi-fi networks. First experiments are presented when a tracked robot is performing surveillance tasks where its state can be changed to tele- operation/videoconferencing mode. The experimental results also show the robot interacting with a reasoning engine in the Cloud.